Enhancement of student learning and attitude towards mathematics through authentic learning experiences - Blum, Kathleen Mary (Curtin University, 2002)
Research suggests that many high school students are not learning mathematics of value from a personal or an employment perspective. School mathematics often consists of applying memorised algorithms to exercises that do not meaningfully connect with the student's experience, and hence do not lead to the construction of meaningful mathematics concepts by the student. Moreover, most high school mathematics curricula give students a false idea of the essence of mathematics: Instead of understanding mathematics as another powerful lens through which to view the world, and a creative, enjoyable endeavour, it is seen as mere calculation or esoteric gobbledegook. Authentic learning experiences involve a different perspective on both what passes as mathematics and how students learn to mathematise. The study examined high school mathematics knowledge from several perspectives, and sought, through an empirical study, to enhance student learning and attitude towards mathematics through authentic learning. A class of Year 8 students learnt several units of mathematics primarily by authentic methods, using problems or interesting phenomena in the students' own experience, or otherwise meaningful to the student. Qualitative data was collected by multiple methods, including video recordings. Surveys were administered to five classes of Year 8 students and their parents at the beginning and at the end of the semester in which most of the empirical research took place. This allowed a comparison of attitudes towards mathematics between the experimental class and the other classes. A comparison of achievement was also made.The results indicate that employing authentic learning experiences may enhance learning and attitude towards mathematics. However, prior transmission teaching methods presented a significant barrier to student acceptance of authentic learning. Furthermore, there remain grave problems with other aspects of current high school mathematics curricula, specifically the mathematics content and the assessment style, which act against the full implementation of authentic learning. These problems are investigated and possible future paths considered.